Review of the state of world marine capture fisheries management : (FAO, 2006)
During the first half of the 1990s, in response to the increasing concern about many of the world's fisheries and following the United Nations Conference on Environment and Development (UNCED), a number of international fisheries instruments provided an impetus for countries to strengthen their fisheries management. A key step in supporting such efforts is the development of more detailed, systematic and comparable information on fisheries environments and management trends. "The State of World Marine Capture Fisheries Management Questionnaire" was developed by FAO in 2004 to help meet this need. The results have been grouped by region and are reported in this publication. Today, we are able to look back to see how countries responded, to examine whether more fisheries are managed and to determine whether the management tools and strategies employed have improved the overall situation in marine capture fisheries. Trends in legal and administrative frameworks, management regimes and status of marine capture fisheries are analysed for 32 countries in the Indian Ocean and presented as an easy-to-read and informative reference for policy decision-makers, fishery managers and stakeholders.